Interacting dark sector with variable vacuum energy - Chimento, Luis Pascual (2013)
We examine a cosmological scenario where dark matter is coupled to a variable vacuum energy while baryons and photons are two decoupled components for a spatially flat Friedmann-Robertson-Walker spacetime. We apply the χ2 method to the updated observational Hubble data for constraining the cosmological parameters and analyze the amount of dark energy in the radiation era. We show that our model fulfills the severe bound of Ωx(z≃1100)<0.009 at the 2σ level, so it is consistent with the recent analysis that includes cosmic microwave background anisotropy measurements from the Planck survey, the Atacama Cosmology Telescope, and the South Pole Telescope along with the future constraints achievable by the Euclid and CMBPol experiments, and fulfills the stringent bound Ωx(z≃1010)<0.04 at the 2σ level in the big-bang nucleosynthesis epoch.